Perceptions and Reality of Overfishing: Evaluating Shifts in Fish Species Composition and Livelihood Impacts on Pemba Island, Zanzibar - Sixbert Joachim Msambichaka (Eastern African Journal of Humanities and Social Sciences)
This study was conducted at Pemba Island, Zanzibar. It evaluated the perceived effects of overfishing on shifts in the species composition of fish. 368 people who engage in fishing-related activities participated in a cross-sectional survey and gave different perspectives on ecological change and their local experiences. The results showed that 55.2% of those surveyed said that the species of fish has reduced significantly in the last several years. A substantial contributing factor that was linked to a 25.2% rise in the probability of documented species changes was overfishing. Residence, marital status, gender, years of fishing experience, and frequency of fishing were additional significant factors. The likelihood of these changes being perceived was lower among infrequent fishermen, but higher among older male fishers, urban dwellers, and those with greater fishing experience. Pemba Island's marine resources to remain ecologically and economically sustainable, the study emphasises the urgent need for inclusive and sustainable fisheries management systems that incorporate local knowledge and address the social aspects of overfishing.